Protocolo del Centro Andaluz de Medicina del Deporte, para el cribado de la infección por SARS-CoV-2 en deportistas - Beas-Jiménez, J. D.; Fernández de Alba Sánchez, M.C.; Vaz-Pardal, M. C.; Jiménez-López, L. (Revista Andaluza de Medicina del Deporte, 2020)
Objective: to publicize the protocol designed by the Andalusian Center for Sports Medicine, for the screening of SARS-CoV-2 infection in athletes.Method: consensus of the professionals of the Andalusian Center for Sports Medicine after reviewing the existing protocols for screening the clinicalsituation COVID-19.Results: a protocol for the screening of SARS-CoV-2 infection in athletes has been developed, which consists of an action plan, a screening questionnaire, a database that includes the entire monitoring of athletes and a system to issue a fitness report to the athlete.Conclusion: a complete protocol for the screening of COVID-19 is proposed, specifically designed for its application in the field of sport, to promote safe sports practice.